Severity of thrombocytopenia and its outcome in preterm and term neonates admitted in neonatal intensive care unit in a rural tertiary care hospital - Reddy, P. Krishnakanth; Kondle, Vamshi Krishna (International Journal of Contemporary Pediatrics, 2019)
Background: Detection of thrombocytopenia is a useful initial assessment for sick neonates, and it is considered as one of the complications of the disease process. Methods: The present study was a prospective hospital based observational study done in 60 neonates in the department of Paediatrics, KIMS, Narketpally during the period of October 2016 to September 2018. Results: The proportion of babies with thrombocytopenia admitted to the NICU was 10.9%. out of the sixty newborns with thrombocytopenia, 31(51.7%) were term babies and 29(48.3%) babies were preterm. Out of 29 preterm babies 3 (5%) were extremely preterm, 5 (8.3%) were very preterm and 21(35%) babies were moderate to late preterm. 32 babies (53.3%) had mild thrombocytopenia, 14 babies (23.3%) babies had moderate thrombo cytopenia and 14 babies (23.3%) had severe thrombocytopenia. The most common etiologic association with thrombocytopenia was septicemia (60%) followed by birth asphyxia (23.3%), maternal Pregnancy induced Hypertension (18.3%), both Disseminated intravascular coagulation and Meconium aspiration syndrome were 6.6% and Necrotizing enterocolitis was 3%. Among the 60 babies admitted with thrombocytopenia, the most frequently seen symptom was not feeding well (35%) and lethargy (33.3%) in all three groups that is babies with mild, moderate, and severe thrombocytopenia. Mortality rate among severely thrombocytopenic neonates was significantly higher (57.14%). Conclusions: Low platelet count was an independent risk factor for poor outcome in our study. Hence it could be used as a prognostic indicator in thrombo- cytopenic neonates.